TssA forms a gp6‐like ring attached to the type VI secretion sheath. (10th June 2016) - Planamente, Sara; Salih, Osman; Manoli, Eleni; Albesa‐Jové, David; Freemont, Paul S; Filloux, Alain
Abstract: The type VI secretion system (T6SS) is a supra‐molecular bacterial complex that resembles phage tails. It is a killing machine which fires toxins into target cells upon contraction of its TssBC sheath. Here, we show that TssA1 is a T6SS component forming dodecameric ring structures whose dimensions match those of the TssBC sheath and which can accommodate the inner Hcp tube. The TssA1 ring complex binds the T6SS sheath and impacts its behaviour in vivo . In the phage, the first disc of the gp18 sheath sits on a baseplate wherein gp6 is a dodecameric ring. We found remarkable sequence and structural similarities between TssA1 and gp6 C‐termini, and propose that TssA1 could be a baseplate component of the T6SS. Furthermore, we identified similarities between TssK1 and gp8, the former interacting with TssA1 while the latter is found in the outer radius of the gp6 ring. These observations, combined with similarities between TssF and gp6N‐terminus or TssG and gp53, lead us to propose a comparative model between the phage baseplate and the T6SS. Synopsis: TssA1 is a multimeric component of the T6SS that forms ring‐shaped structures positioned at one end of the T6SS sheath and shares sequence and structural similarity with the baseplate protein gp6 of the T4 phage. TssA1 is an essential core component of the T6SS which forms dodecameric ring‐shaped complexes. The TssA1 ring binds the tail‐like structure of the T6SS and impacts the assembly of the TssB1C1 sheath in vivo . TssA1 displays sequence and structural similarity with the C‐terminal moiety of the T4 phage baseplate component gp6. TssA1 interacts with other baseplate components of the T6SS, including TssK1 that binds the T6SS inner membrane complex. Sequence comparison between T6SS and T4 phage components suggests the existence of a comparable T6SS baseplate organization. Abstract : TssA1 is a multimeric component of the T6SS that forms ring‐shaped structures positioned at one end of the T6SS sheath and shares sequence and structural similarity with the baseplate protein gp6 of the T4 phage.